ANALYTICAL HIERARCHY PROCESS APPROACH ON CONSUMER PURCHASE DECISION IN CHOOSING CHINESE RESTAURANT IN MANADO (CASE STUDY: AFUI, NEW MIE JAKARTA, AND SAMRAT ABADI) - Macawalang, Andre H.S; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Nowadays, Chinese restaurant are rapidly growing up. In comparison to regular restaurants, Chinese restaurants possess certain sociological and cultural elements that make them special for their guests in ways that cannot be found in regular restaurants. In Manado, there are three Chinese restaurant that are most visited by costumer which are Afui, New Mie Jakarta, and Samrat Abadi. All the restaurant are in the Samrat Street. Buying decision is consumer action to choose product from several alternate products which will be used by the consumer. Some factors that can drive consumer decision in culinary business: price, brand image, cleanliness, service quality, atmosphere, and menu design. The purpose of this study is to know the most important criteria for consumer in choosing Chinese restaurant in Manado and which restaurant is the most preferable. This research used Analytical Hierarchy Process with total sample of 50 respondents. The result shows that the most important factor is cleanliness. Then atmosphere, service quality, brand image, price and menu design is the last place. Samrat Abadi is the most preferred Restaurant among the other alternatives. The restaurant should keep their place clean. Afui and New Mie Jakarta, have to improve their performance or service quality, adding more promotions and make some different thing which is unique or something that the competitors does not have.Â Keywords: consumer purchase decision, analytical hierarchy process